Effect of electrochemical treatment on substrate adhesion strength in the restoration of motor vehicle parts operating under hydroabrasive wear - A. N. Kotomchin (Вестник СибАДИ, 2022)
Introduction. In the process of chrome plating of car parts, it is necessary to obtain high-quality chrome coatings with specified physical and mechanical properties. Therefore, electrochemical treatment before coating plays a crucial role in the formation of coatings with high contact strength and wear resistance. The study of the electrochemical treatment process will make it possible to develop recommendations for obtaining high-quality coatings when restoring vehicle parts.Materials and methods. To conduct reliable research, the necessary equipment was used, which made it possible to obtain data with the necessary accuracy. Also, modern data processing tools were used to carry out mathematical processing, which excluded the possibility of error and thereby obtain the dependences of factors with the necessary accuracy.Results. When using the developed new chromium plating electrolyte, it became necessary to conduct studies of the modes and time of electrochemical treatment before coating parts made of steels containing chromium and hardened to HRC 55-60 hardness. Based on the results obtained, it was found that the greatest adhesion strength will be when using electrochemical etching with a current density of 130-140 A/dm2 and a holding time of 60-70 s. It is also necessary to activate in the chrome plating solution itself with an anode current density of 70-80 A/dm2 and a time of 30-40 s, with a sharp switch to the chrome plating mode. Conclusions are drawn on the optimization of electrochemical surface treatment before chrome plating, in order to obtain the greatest adhesion to the substrate. Discussion and conclusion. As a result of the conducted studies of the electrochemical processing of the part before chrome plating, it was possible to obtain that when restoring parts operating under waterjet wear, it is necessary to observe the specified conditions for obtaining high-quality coatings with high adhesion strength while maintaining high physical and mechanical properties of the coating.